주민참여예산제도에 관한 인식차이 - 김겸훈(Gyum-Hun Kim); 이은구(Eun-Ku Lee) (한국콘텐츠학회 논문지, 9(2), 2009)
In contrary to the expectation of which it has a role to increase the transparency of and the responsibility of self-governing, the participatory budgeting even though aggravates perfunctoriness of participation and local conflicts in Korea. The problems are caused not from the institutional vices of participatory budgeting but from others which each part of people, participating in the budgeting process, have a misunderstanding on the participatory budgeting. Under the consideration that the misunderstandings of citizen and local officials are one of main reasons of a derailing of the participatory budgeting, the study aims to examine empirically the gap between the citizen's understanding on the participatory budgeting and the official's, focused on Daeduck-ku, Daejeon. 주민참여예산제도는 참여를 통한 자치의 투명성과 책임성의 제고라는 본래의 기대와 달리 참여의 형식화나 새로운 형태의 주민갈등이 나타나는 등 역기능도 공존한다. 이에 본 연구는 한국식 주민참여예산제 운영과정에서 관련 당사자로 부딪치는 공무원과 주민참여위원들 간에 어떤 인식적 차이가 존재하고 있는가를 실증적으로 확인코자 하였다. 그 결과 주민참여위원들은 주민참여의 활성화와 예산낭비의 억제 및 예방 등에 긍정적인 인식을 갖고 있는 반면 공무원들은 인기영합적 예산편성과 예산수요의 증가, 집행부 권한 약화와 의사결정의 곤란 및 참여의 형식화 등을 걱정하였다. 이와 같은 분석결과가 시사하는 점은 우선 공무원 집단의 경우 이 제도가 지방의회의 예산심의권을 침해 할 것이라는 인식에서 본 것처럼 제도에 대한 잘못된 이해와 기존의 행정행태에 기반한 인식에 의존하고 있고, 주민참여위원의 경우도 제도에 대한 잘못된 인식을 갖고 있기 때문에 이를 바로잡는 것이 시급한 과제라는 점이다.